Surgical harm, consent, and English criminal law: When should 'bad-apple' surgeons be prosecuted?. (December 2021) - Mullock, Alexandra
This article examines the legal principles determining when surgical harm becomes a criminal matter. In England and Wales, and other common law jurisdictions, the criminal law has predominantly concerned itself with fatal medical misconduct via the offence of gross negligence manslaughter. The convictions of two surgeons in 2017 (Ian Paterson and Simon Bramhall), for offences against the person, suggests that police and prosecutors have, for the first time, become willing to prosecute surgeons for non-fatal surgical harm. Understanding when non-fatal surgical harm should be treated as a criminal matter is, however, a complex issue. The medical exception to the criminal law legitimizes consensual and reasonable surgical harm. Thus, the question of what is reasonable and what constitutes valid consent is key to determining the parameters of lawful surgery; however, the principles are perplexing and insofar as they may be agreed and understood, they are arguably unsatisfactory. After examining the cases involving serious surgical harm and analysing the doctrines applied, this article argues for a more patient-centred approach. The focus should be on the nature of the harm to the victim, the behaviour of the dangerous surgeon and whether a violation has occurred, rather than on traditional professional assessments, which are unduly deferential to the medical profession.